Hepatoprotective Effect of Echinops tenuisectus (Compositae) on CCl4 Induced Hepatic Damage in Rats - Munaf H. Abdulrazzaq; Enas J. Khadeem; Suhad S. Al- Muhammadi (College of Pharmacy University of Baghdad, 2017)
Flavonoids are known to play a vital role in the management of various liver disorders.They are a large family of compounds synthesized by plants; they belong to a group of natural substances with variable phenolic structures. In this study we aim to scan the types of flavonoids in a newly studied, wild Iraqi plant named Echinops tenuisectus of Compositae family. The medicinal importance of flavonoids on one hand, and the absence of any phytochemical investigation on tenuisectus species of Echinops genus on the other hand, acquired this study itÛ¥s importance. Three flavonoids were identified in the seed,s extract of this plant (Silymarin, Rutin, Quercetin ) by two chromatographic methods, first Thin layer chromatography (TLC) using TLC ready made GF254 plates, UV detector at 254 nm, and two different solvent systems in which the Rf value of the standards (Silymarine, Rutin, Quercetin) matched with the Rf value of the Silymarin, Rutin and Quercetin found in the plant seedÙ«s extract. High pressure liquid chromatography (HPLC) was the other chromatographic method that used to identify the presence of these flavonoids in the plant seed. The plant seed Û¥s aqueous extract was evaluated for its efficacy in rats by inducing hepatotoxicity with CCl4.Single oral dose of 250mg/kg of Seeds Extract was given to ratÛ¥s for 7 days. Serum activities of transaminases (ALT and AST) were used as the biochemical marker of hepatotoxicity. Histopathological changes in ratÙÙs liver section were also examined. The results of the study indicated that, the pretreatment of rats with Echinops extract before the hepatotoxins agent (CCl4) offered a hepato- protective action. Key words: Echinops, Flavonoids